Cinema of the Arab World
XXXIV, 422 p. 43 illus., 23 illus. in color.
Keywords: "Ginsberg and Lippard have managed something rare: a riveting collection of essays with a consistently strong voice throughout. These chapters treat a diverse archive of films, filmmakers, and contexts with theoretical and historical depth and an urgency of interpretation, challenging the enormous gaps in our knowledge of Arab cinematic expression. Not only is this book indispensable for courses on Arab cinema, it will undoubtedly prompt new routes of inquiry for researchers, teachers, and viewers alike." — Peter Limbrick, University of California-Santa Cruz, USA “Cinema of the Arab World fills gaps in the literature and re-envisions the ways in which Arab cinema has been looked at previously. It succeeds by avoiding conforming to the stereotypical molds that guide some scholarship about the region. The mix of established scholars as well as young researchers, and the inclusion of different philosophical and critical theories and methodologies, make this book indispensable to anyone interested in understanding contemporary Arab cinema. Highly recommended." — Orayb Najjar, Northern Illinois University, USA This volume engages new films and modes of scholarly research in Arab cinema, and older, often neglected films and critical topics, while theorizing their structural relationship to contemporary developments in the Arab world. The volume considers the relationship of Arab cinema to transnational film production, distribution, and exhibition, in turn recontextualizing the works of acknowledged as well as new directorial figures, and country-specific phenomena. New documentary and experimental practices are referenced and critiqued, while commercial cinema is covered both as an industrial product and as one of several instances of contestation. The volume thus showcases the breadth and depth of Arab film culture and its multilayered connections to local conditions, regional affiliations, and the tendencies and aesthetics of global cinema.